Viking Vik and the chariot race - Rayner, Shoo (London: Orchard, 2008)
FICTION. Great books for boys! Fast-paced and exciting. Join Viking Vik as he faces challenges with his best pal Wulf. Their adventures on the mountains, the wild seas and in the Underground Kingdom will delight new readers!
Keywords: Adventure stories